In-depth assessment of structural and mechanical properties of copper slag as an eco-friendly alternative construction material - Noufal, E. Rahmathulla; Kasthurba, A.K.; Sudhakumar, J.; Manju, Unnikrishnan (Journal of Structural Engineering, 2024)
Two significant problems that require immediate attention are (i) the rising demand for building materials to meetthe expanding demands of the construction industries, and (ii) the rising production of industrial wastes that mustbe properly disposed of as a result of rapid industrialization and growing urbanization. Therefore, researchers havebeen working continuously to find solutions to these issues and have been investigating the potential uses of industrialwaste slags as an alternative, sustainable construction material. Given that the slags can vary in their chemicalcompositions and may contain large concentrations of heavy metals, rendering them toxic and dramatically modifyingtheir properties, a comprehensive study of the slag attributes is crucial in this context. As a substitute for river sand asfine aggregate in reinforced cement concrete, copper slag, a byproduct of copper smelting and refining, is discussed indetail here in terms of its structural, mechanical, physical, and chemical qualities. In order to determine the electronicstructure, surface atomic concentrations, and phase analysis of the slag concrete, X-ray photoemission spectroscopyanalysis, powder X-ray diffraction measurements, direct shear analysis, ultrasonic pulse velocity analysis, and rapidchloride permeability tests were conducted.